Mitochondrial Function in Lung Health and Disease - Natarajan, Viswanathan; Parinandi, Narasimham L. (Respiratory Medicine, 2014)
Mitochondria, often referred to as the "powerhouses" of the cell, generate adenosine triphosphate (ATP) by oxidative phosphorylation or OXPHOS, and maintain cellular homeostasis. In addition to generating ATP, mitochondria are involved in regulation of cell cycle, proliferation, free radical production, innate immune responses and apoptosis.  Mitochondrial Function in Lung Health and Disease fills the current gap in the literature and outlines the growing clinical relevance of mitochondrial dysfunction.  Currently, there is no overview on the role of mitochondria in pulmonary diseases and this volume focuses on the mitochondrial metabolism, redox signaling, and mechanisms of mitochondrial pathways in lung injury, inflammation, repair and remodeling.  Furthermore, in addition to their well-recognized role in cellular energy production and apoptosis, mitochondria appear to play a role in many respiratory diseases and lung cancer. Chapters are written by top notch researchers and clinicians and outline the evidence for mitochondrial biogenesis in inhalational lung injury, COPD and asthma.  .